KEPASTIAN HUKUM DAN PENGAKUAN PARA PIHAK HASIL PENGUKUHAN KAWASAN HUTAN NEGARA DI PROVINSI RIAU - Pernando Sinabutar; Bramasto Nugroho; Hariadi Kartodihardjo; Dudung Darusman (Jurnal Analisis Kebijakan Kehutanan, 2015)
Legal certainty and legitimacy of forest area can be gained through the gazettment process of forest area that starts from the designation, boundary demarcation, mapping, and ends up with the establishment. In Riau Province, these processes are stagnant, and, therefore, the legal certainty and legitimacy is difficult to achieve. What is really happenned is something that needs to be answered in this study. By using the analysis of strategy typology and descriptive qualitative analysis, this study has found that the gazettment issues of forest area consisted of three aspects, namely: designation, boundary demarcation and establishment. Social conflict has been accumulated along the gazettment process, so that the legal certainty did not lead to legitimacy. This problem happened due to: claims avoidance (PTB) to avoid failure in boundaries determination; policy narrative of the boundaries are not informed to community; inconsistency between the objective of boundary demarcation with the implementation; domination of all informed knowledge and information (BPKH); stages of gazettment were done just to fulfill administrative procedure; BPKH tasks issues; and state forest area regarded as the common pool resources (CPRs). This result proves that the improvement of government, policy in gazettment of forest area is seriously required.